(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
As one of the most influential political events in 21st-century Europe, Brexit was not merely a political, economic, and administrative event but also a cultural phenomenon. In the context of this historical backdrop, Ali Smith’s Autumn (2016) emerged as the first literary work to directly engage with the issue of Brexit, garnering significant critical and public attention upon its publication. Significantly, this study reveals that the “intergenerational desire” in Autumn is not expressed through direct character interactions but rather is mediated through a reconfigured temporality constructed via natural imagery, particularly that of the “thing”- “tree”. Furthermore, the novel exposes the social fragmentation and relational complexities resulting from the Brexit referendum, revealing that while it ostensibly addresses ethnic tensions, its deeper critique centers on issues of class identity. Focusing on the arboreal motif, this paper examines how the novel articulates the intellectual woman-Elisabeth’s distinctive vision of social order through three interrelated dimensions—intergenerational desire, the politics of time, and ethnic discourse—thereby proposing potential pathways for reimagining post-Brexit British society.